Preliminary phytochemical and physicochemical evaluation of Carallia brachiata (Lour.) Merr. leaves - Julfikar Ali Junejo,Kamaruz Zaman,Mithun Rudrapal,Prodyut Mondal,Khumantham Deepak Singh,Vinod Kumar Verma (Journal of Applied Pharmaceutical Science, 2014)
In the present study, the preliminary phytochemical and physicochemical studies including fluorescence and thin layer chromatographic analyses of the leaves of Carallia brachiata (Lour.) Merr. (Rhizophoraceae), an Indian medicinal plant used traditionally in the treatment of a variety of human disorders, were carried out with an objective to standardize the plant/plant part (leaves) to be used either as crude drug or in the form of herbal medicine, considering the quality and safety requirements of herbal drugs as per pharmacopoeial standards and/or WHO guidelines.
Keywords: Carallia brachiata,Physicochemical evaluation,Standardization,Herbal drugs.